PREMISES OF ACTIVATION OF MENTAL ACTIVITY IN THE EDUCATION PROCESS - Juodraitis, Adolfas (Acta Paedagogica Vilnensia, 2007)
Accumulation of the information and its volitional reproduction is significant for the social and personal functioning of mentally retarded children. These processes are impeded and interfere with successful personal socialization. The particularities of cognitive processes (and especially memorial processes) determine forming and purposeful appliance of different competences (behavioral, professional, and communicative) in person’s social life and displaced development of social needs. The way of different activating in the educational processes trying to change of quantities and qualitative parameters of remembrance dynamic, became a significant component in the modeling of new tendencies in life quality alteration of disabled. The research proves that earlier performed task can be assessed as an object of remembrances (and especially it is obvious in the activity of mentally retarded) and as a remembrance tool of performed result, as well. Essentially the remembrance of the performed activities result includes a lot of mental acts (dynamic of action, situation, and different barriers) which stimulates mnemic processes during saving and reproduction of obtained information. After the experiment with the middle age school mentally retarded children we find out that it was easier to remember (immediate and deferred reproduction) performed action and the result of remembrance efficiency was better. It is regular that comparing results of control and experimental groups difference in all reproduction tasks was significant (from p < 0,01 to p < 0,001). And increasing efficiency of remembrances (in this case the verbal stimulating material) shows the potential of learning abilities. The analyses of the research let us draw conclusion that applied methods of mnemic activation in educational processes of mild mentally retarded children determinates higher level of information mastering and preservation.
Keywords: remembrance processes; memory; done activity; result of an activity; activating intellectual activities